Estetika Simbolik pada Desain Bangunan Komersil di Kawasan Perdagangan Cihampelas - Morika, Doni (Bina Nusantara University, 2012)
The notion of aesthetics so far did not produce a conclusion crystallized from various points of view offered by observer. It came from the standpoint of behavioral and psychological environment to obtain the aesthetic sense which was based on the notion of meaning, perception, and aesthetic experience. In the philosophy of beauty